The Effect of Communication on Employee and Company Performance: A Systematic Literature Review (SLR) - Ningrum, Dewi Ayu Dyah; Antara, Radittya Mahasputra; Sopiah (PT Maju Malaqbi Makkarana, 2025)
Communication is fundamental to humans. With communication, there will be cooperation, especially in this research is cooperation in an organization. Without communication an organization will not achieve their goals. An organization has diverse individuals and allows for conflict when there is poor communication. So this study aims to investigate and synthesize publications related to internal communication and its effect on employee performance and company performance. This research uses the SLR method. In this study, articles were obtained from the Emerald and Science Direct journal databases with topics and keywords communication, organizational communication, employee performance, company performance. The included articles are articles published between 2020 and 2025. There were 20 articles analyzed and quality assessment was also carried out. The results of the synthesis in this study are that internal communication affects employee performance in relation to their motivation and satisfaction or well-being at work. Internal communication also affects the performance of the company, which is related to the legitimacy of the company. The results of this study can be used as a new view for further research to explore more deeply the effect of internal communication on company performance.